Functional physical condition in institutionalized elderly adults - Benavides-Rodríguez, Cindy Lorena; García-García, Jose Alexander; Fernandez, Jairo Alejandro (Universidad y Salud, 2020)
Introduction: Quantification of the functional physical condition (FPC) in the elderly population is an important indicator to define their state of health, level of dependence, and quality of life. Objective: To determine FPC in a group of elderly people residing at nursing homes in the city of Bogotá (Colombia). Materials and methods: Body composition variables were estimated by anthropometry. The functional physical condition was assessed by the Rikli and Jones Senior Fitness Test battery. Results: 253 older adults (42.6% men and 57.3% women), their age (75.5±9.6), and BMI (24.9 ±3.6) were evaluated. Functional physical condition values were: getting up and sitting down (10.9±3.6 for men and 10.6±3.5 for women), arm flexion (13.3±3.3 men and 11.7±3.8 women), trunk flexion (-11.4±8.2 men and -1.1±4.8 women), joining hands (-16.5±10.7 men and -7.3±6.3 women), aerobic capacity (77.4±13.6 men and 63.9±14.2 women), and agility and balance (7.5±2.3 men and 7.6±2.4 women). Conclusions: Institutionalization of the elderly has a negative impact on their functional physical condition. In particular, it affects their strength, agility and balance, which increases the risk of falls and physical disability.